PERLINDUNGAN HUKUM TERHADAP ANAK DIBAWAH UMUR SEBAGAI KORBAN PEMERKOSAAN - Natashya Natashya; Hery Firmansyah (UNES Law Review, 2023)
Rape is increasingly occurring with perpetrators who are unaware of the place and time. Protecting minors who become victims is a government priority. This study uses a normative research method, referring to primary and secondary legal sources. Law Number 35 of 2014, which amends Law Number 23 of 2002 concerning Child Protection, regulates legal protection for child victims of rape. Victims can file for restitution, receive medical assistance, and undergo psychosocial rehabilitation. Rapists can be sentenced to a maximum of 15 years in prison and a minimum of 5 years, as well as fined up to Rp.5,000,000,000.00. Therefore, it can be concluded that child rape victims receive strong legal protection under the Child Protection Law. Additionally, they also receive the necessary assistance for physical and psychological recovery. On the other hand, rapists face severe sanctions commensurate with the crime committed. This research has important implications for raising public awareness about the importance of protecting child rape victims and ensuring consistent enforcement of existing laws.